ANALISIS KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA: KAJIAN LITERATUR TERHADAP PROBLEMATIKA, IMPLEMENTASI, DAN SOLUSI STRATEGIS - Sam Sukur Rahman; Winengan; Hadi Kusuma Ningrat (Universitas Islam Negeri Mataram, 2026)
This study aims to analyze Islamic education policies in government-managed formal Islamic educational institutions in Indonesia, focusing on the problems of policy implementation, management challenges, and strategic solutions for improving educational quality. This study focuses on the context of Islamic education in madrasahs as part of the national education system to obtain a more focused and contextual analysis.. The study uses a qualitative approach with a library research method, with data sourced from books, scientific journals, and relevant policy documents. Data collection techniques were carried out through documentation, while data analysis used content analysis techniques to systematically review and synthesize various research findings. The results of the study indicate that Islamic education policy in Indonesia still faces various problems, including dualism in the education system, low quality human resources, weak institutional governance, and a lack of adaptation to developments in the digital era. Policy implementation also shows a gap between formulation and implementation, which is influenced by a top-down approach, limited resources, and contextual factors in the field. Therefore, strategic solutions are needed in the form of strengthening the integration of the education system, improving the quality of human resources, improving the management of educational institutions, and adaptive policy transformation to technological developments.